STATUS MIKROBIOLOGI DAGING BROILER DARI PASAR – PASAR TRADISIONAL DI KOTA METRO - Muhammad Edwin; Purnama Edy Santosa; Rr. Riyanti (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This research aimed to determine microbiologic status observation on the broiler chiken of the traditional markets in the city of Metro. The study was conducted from Desember 2015 - Januari 2016 in the Laboratory Veterinerr Region III Office of Lampung. The study used a random sampling technique and used 22 samples from 4 traditional markets of Cendrawasih, 16 C Margorejo, 24 Margorejo, and Tejo Agung. Parameters of microbiologic status data were analyzed using binominal test concern their each parameters (National Standardization Agency (NSA) 7388:2009). The result showed that TPC (Total Plate Count) was same with standard, Coliform up standard, Salmonella sp. was same with standard. Key words: Microbiologi Status, Broiler, Traditional Market, Metro City